Implant Stability Changes for Nonsubmerged and Submerged Protocols for a Single Implant Mandibular Overdenture Using Ball Attachment - Ahmed Salah; Karim Foda; Mohamed Farouk Abdalla; Marwa Abdel Aal; Amr Naguib; Nouran Abdel Nabi (Hindawi Limited, 2021)
Objectives. To compare the changes in implant stability for the nonsubmerged (NS) and submerged (S) protocols for the single implant retained mandibular overdenture using ball attachment throughout a 24-month follow-up. Materials and Methods. Eighty completely edentulous patients were seeking to improve retention of their lower complete denture by installing a single implant in the midline of the completely edentulous mandible. At the day of implant installation, patients were randomized into 2 groups using sealed envelopes: the nonsubmerged (NS) and submerged (S) group. After a 3-month healing period, all patients were randomized using sealed envelopes into ball attachment and CM-LOC attachment. The Periotest readings (PTV) was recorded using the Periotest M device and was recorded every 3 months for the first year and then annually in the second year. The scope of this clinical trial focused only on results of the ball attachment. The Mann-Whitney U test was used for comparison between study groups for independent samples. Two-sided p values less than 0.05 was considered statistically significant. Results. There was no statistically significant difference in the mean change in PTV reading between the NS and S group at the different follow-up intervals. Initially, at the day of pickup (baseline) and 3-month follow-up, the mean PTV reading for the NS was greater than that of the S group (−4.471 ± 1.489, −4.391 ± 1.4727 (p=0.913)), while the S group has shown a greater improvement in PTV than the NS group after 6-month follow-up and continued throughout the 24-month follow-up (−5.730 ± 1.7804, −50855 ± 1.2581 (p=1)). Conclusion. Both the nonsubmerged and the submerged healing protocol have shown reliable Periotest readings using ball attachment for a single implant retained overdenture. The submerged group has resulted in a greater improvement in Periotest readings after the 12- and 24-month follow-up period when compared to the nonsubmerged group although this improvement was not statistically significant.